2022
DOI: 10.3390/ijerph19127528
|View full text |Cite
|
Sign up to set email alerts
|

Association between Age-Friendliness of Communities and Frailty among Older Adults: A Multilevel Analysis

Abstract: An age-friendly environment is one of the measures of healthy aging. However, there is scarce evidence of the relationship between the age-friendliness of communities (AFC) and frailty status among Chinese older adults. This study aims to examine this relationship using a multilevel analysis with the data of a cross-sectional study conducted among 10,958 older adults living in 43 communities in four cities in China. The validated Age-friendly Community Evaluation Scale and Chinese frailty screening-10 Scale (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The physical and communication behavioural modifications can lead to linked improvements in both mental and cognitive wellbeing for older adults [ 74 ]. The communications ecology model may be relevant to an age-friendly community [ 75 ]. A previous study also showed that older adults with greater use of adaptation via communications may cope and have defense mechanisms across adulthood [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…The physical and communication behavioural modifications can lead to linked improvements in both mental and cognitive wellbeing for older adults [ 74 ]. The communications ecology model may be relevant to an age-friendly community [ 75 ]. A previous study also showed that older adults with greater use of adaptation via communications may cope and have defense mechanisms across adulthood [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…24 Yang et al (2023) also found no association between gender and frailty in CKD patients. 25 However, Xu et al (2022) and Li et al (2021) show a strong correlation between gender and frailty in the geriatric population. 27,28 The theoretical perspective supports the idea that frailty risk often increases in females.…”
Section: Discussionmentioning
confidence: 98%
“…25 However, Xu et al (2022) and Li et al (2021) show a strong correlation between gender and frailty in the geriatric population. 27,28 The theoretical perspective supports the idea that frailty risk often increases in females. 17 Nutritional status is a significant risk factor with a strong correlation.…”
Section: Discussionmentioning
confidence: 98%
“…For planning and evaluation purposes, it is important to determine the mechanisms that account for these links in different populations. Xu et al [ 42 ] found that a higher level of age-friendliness in a community is associated with lower odds of frailty, for example. Services to detect and treat mental health problems, which may directly and indirectly affect health and physical activity, cognitive function, and premature mortality are also important areas of prevention and intervention [ 43 ].…”
Section: Discussionmentioning
confidence: 99%